Development and validation of UPLC method for simultaneous estimation of Efavirenz and Lamivudine in pharmaceutical formulations - Madhusudhanareddy Induri,Bhagavan Raju Mantripragada,Rajendra Prasad Yejella (Journal of Applied Pharmaceutical Science, 2016)
An accurate and precise UPLC method was developed for the simultaneous estimation of efavirenz and lamivudine in pharmaceutical dosage forms. The chromatographic analysis was performed on Acquity UPLC BEH Shield RP18 (50 × 3 mm, 1.7 µm) column with mobile phase consisting of 10% acetonitrile in methanol and 10 mM phosphate buffer (pH 4.0) in the gradient mode, at a flow rate of 0.4 mL/min, and eluents monitored at 254 nm. The calibration curves of peak area versus concentration, which was linear from 10-60 µg/mL for efavirenz and 5.0-30 µg/mL for lamivudine, had regression coefficient (r2) greater than 0.999. The method had the requisite accuracy, precision, and robustness for simultaneous determination of efavirenz and lamivudine in tablets. The proposed method is simple, economical, accurate, and precise and could be successfully employed in routine quality control for the simultaneous analysis of efavirenz and lamivudine in pharmaceutical formulations.
Keywords: Efavirenz,Lamivudine,UPLC,Method Development.